FUNDAMENTALISM REVISITED : Fundamentalism as a Counter- Culture to Modernity and its Values - Purwadi, Y. Slamet (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2008)
One of the most prominent and haunting cultural phenomenain our times is 'fundamentalism'. Its prominence, complexityand negative impacts render fundamentalism worth revisiting.Beyond its definitions, forms and enigmas, the existence offundamentalism compels us to reflect on some significantaspects of our age. I assume that fundamentalism is not athrowback to a tradition, but that it is in a dialectic relationshipwith modernity. I stress, therefore, the points of convergencebetween fundamentalism and modernity. The overlappingparadigms of fundamentalism and modernity are exploredthrough a socio-cultural and philosophical approach. Throughan elaboration of the function of fundamentalism as a culturalopposition, the paper concludes with a postmodernistapproach toward a new sensibility for 'difference and diversity'.